2018
DOI: 10.1645/17-123
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Gastrointestinal Parasites from Ansell's Mole-Rat (Fukomys anselli) in Zambia

Abstract: The endoparasite fauna of Ansell's mole-rat, Fukomys anselli (Burda, Zima, Scharff, Macholán and Kawalika) (Rodentia, Bathyergidae), was studied for the first time near Lusaka, Zambia. We recovered 7 endoparasite taxa including 5 nematodes ( Hexametra sp.; Protospirura numidica Seurat, 1914; Protospirura muricola Gedoelst, 1916; Protospirura sp.; and Mammalakis zambiensis Junker, Lutermann and Mutafchiev, 2017 ); and 2 cestodes ( Inermicapsifer sp. and Rodentolepis cf. microstoma Dujardin, 1845) from 272 indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“… Lutermann et al (2018) reported the following gastrointestinal parasites from Ansell’s mole-rat, F. anselli in Zambia. Those include Hexametra sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Lutermann et al (2018) reported the following gastrointestinal parasites from Ansell’s mole-rat, F. anselli in Zambia. Those include Hexametra sp.…”
Section: Resultsmentioning
confidence: 99%
“…Junker et al (2017) described a new species of ascaridid nematode, Mammalakis zambiensis acquired from the large intestine and cecum of Ansell's mole-rat, Fukomys anselli (Burda et al, 1999), captured from west of Lusaka at Mukulaikwa Farm Block, Zambia. Lutermann et al (2018) reported the following gastrointestinal parasites from Ansell's mole-rat, F. anselli in Zambia. Those include Hexametra sp.…”
Section: Ethiopian Subterranean Rodent Endoparasitesmentioning
confidence: 99%